Analisis Pengendalian Kualitas Produk Sanitary Ware Dengan Pendekatan Metode FMEA di PT. XYZ - Siregar, Khawarita; Siregar, Syahrul Fauzi (Sanata Dharma University, 2016)
PT. XYZ is a company engaged in manufacturing of sanitary ware products. Various obstacles are faced by PT. XYZ in the course of its production, one of which is the problem of the quality of products produced from every production process. Based on historical data from July 2014 – June 2015, the percentage of defect for C models squat toilets reached 20.26%. The company wants the upper limit of defects products only reached 12% for each period of production. Based on previous research, there are two dominant types of defects are cracked/broken and uneven color. Therefore needed improvement through analysis of quality control approach FMEA method and ANOVA. The result of FMEA for cracked/broken defects obtained failure mode is the temperature and duration of combustion products are not appropriate (RPN numbers amounted to 648) and for uneven color obtained failure mode is glazed improper composition (RPN numbers of 576). This study also will provide corrective suggestions through the design of experiments by ANOVA method. The results of the experiment with the design of interaction factor ANOVA showed that long combustion products, glazed composition and temperature of the combustion products provide a significant effect on the amount of product defects